Integrating Peace Education in Social Studies and Students’ Social Cohesion: an Explanatory Sequential Mixed-Method Study - Jainee E. Galapon; Randy D. Punzalan (Edukhasi: Jurnal Inovasi Pendidikan, 2026)
This study aimed to examine the integration of peace education in Social Studies and its influence on students’ social cohesion. Specifically, it determined the level of integration of peace education in terms of cooperative learning, conflict resolution, and civic awareness, and assessed students’ social cohesion in terms of interpersonal relationships, empathy, and sense of belonging. The study employed an explanatory sequential mixed-method design, where quantitative data were collected through a survey questionnaire administered to Grade 6 students in selected public elementary schools in Cabuyao, Laguna, followed by qualitative data from teacher interviews to support and explain the results. The research instrument underwent validation and reliability testing, yielding acceptable Cronbach’s alpha values. Quantitative data were analyzed using weighted mean and correlation analysis, while qualitative data were analyzed through thematic analysis. Results revealed that peace education was integrated at a very high level across all measured dimensions. Similarly, students demonstrated a very high level of social cohesion, particularly in interpersonal relationships, empathy, and participation within the school community. Furthermore, findings indicated a significant relationship between peace education and students’ social cohesion, suggesting that higher levels of peace education integration contribute to stronger social and behavioral outcomes among learners. The study concludes that integrating peace education in Social Studies plays a vital role in fostering positive social values and strengthening students’ sense of belonging. It is recommended that schools enhance peace education implementation through structured instructional strategies and continuous teacher development.